Potential role of N6-methyladenosine modification in the development of Parkinson’s disease - Zhou, Jiale; Han, Yang; Hou, Ruizhe (Frontiers in Cell and Developmental Biology, 2023)
represents the most abundant modification of messenger RNA (mRNA) and is regulated by methyltransferases (writers), demethylases (erasers), and m6A-binding proteins (readers). A dynamic modification process is implicated in nearly every critical stage of RNA metabolism, including mRNA stability, transcription, translation, splicing, nuclear export, and decay. Notably, m6A methylation is significantly enriched in the brain and has recently been shown to be associated with neurodevelopmental disorders and the development of Parkinson's disease (PD). In this review, we summarize the proteins involved in the process of m6A modification and elucidate the emerging role of m6A modification in PD, which could illuminate alternative strategies for the prevention and treatment of PD.